A Unique Dermoscopy Pattern of Solitary Cutaneous Reticulohistiocytosis - Felipe Ladeira de Oliveira; Letycia Lopes Chagas Nogueira; Gabriel Monteiro de Castro Chaves; Mariana Daflon Vinhosa Muniz; Renata Pinto Fernandes Timbó; Mariana Martins Sasse; Carolina Degen Meotti (Hindawi Limited, 2013)
Histiocytosis represents a group of rare disorders characterized by nonneoplastic proliferation of histiocytes and solitary cutaneous reticulohistiocytosis (SCR) is a form of non-Langerhans histiocytosis. SCR consists of small papule, usually single, varying in color from yellow to brownish-red, more frequent in young adults, and uncommon in childhood. We report a case of SCR in an 11-year-old child and emphasize a unique dermoscopy pattern of this lesion and its correlation with clinical and histopathological aspects in the diagnosis.